Experimental investigation of a new derived oleochemical corrosion inhibitor - Mohyaldinn, M.E. (Trans Tech Publications Ltd, 2019)
Most of the corrosion inhibitors that are used in industry contain chemicals that are harmful to health and environment. Corrosion inhibitors derived from green sources are, therefore, believed to be a good option for replacing the chemical corrosion inhibitors. In this work, a green oleochemical corrosion inhibitor derived from Jatropha Curcas is introduced. The paper discusses the methodology of deriving the corrosion inhibitor as well as the experimental test conducted for evaluating its corrosion inhibition efficiency. The new oleochemical corrosion inhibitor was derived via two reactions. Jatropha oil was firstly saponified with sodium hydroxide to yield gras acid and glycerol, which was then esterified with boron fluoride in presence of excess methanol to produce the oil methyl esters, which is used as oleo-chemical corrosion inhibitor. To evaluate the oleo-chemical corrosion inhibitor, the corrosion rate of mild steel in NaCl corrosive medium with CO2 is tested at static condition and two dynamic conditions, namely 500 and 1500 rpm. This is to simulate the transitional and turbulent flow in a pipeline. At each dynamic condition, the proposed corrosion inhibitor was tested at concentration dosages of 0, 50, 100, and 150 ppm. The experiments results revealed a good performance of the new oleochemical corrosion inhibitor. The inhibition efficiency was found to be highly affected by the concentration of corrosion inhibitor. Total corrosion inhibition of the mild steel was noticed by using 150 ppm at dynamic condition of 500 rpm. Â© 2019 Trans Tech Publications, Switzerland